Pharmacy practice and clinical pharmacy research in the Middle East: a scoping review of studies from Bahrain, Iraq, Jordan, Kuwait, Lebanon, Oman, Palestine, Qatar, Saudi Arabia, Syria, United Arab Emirates, and Yemen - Daneh Obaid; Faris El-Dahiyat; Zaheer- (Taylor & Francis Group, 2022)
Background Pharmacy practice research publications has increased significantly in the last decade. This is also true for Middle Eastern countries. Aims The aim of this study was to document and review pharmacy practice literature in the Middle Eastern Arab countries. Materials and methods A scoping review was conducted using PRISMA-ScR guidelines. Medline/PubMed and Scopus were used to screen the articles. All published original research articles concerning any facet of pharmacy practice in 12 Arabic Middle Eastern countries during 2009-2019 were included. A thematic analysis was performed to classify the articles. Results Nine hundred and eighty-one articles were included in this study. Eight themes emerged from the selected articles. Medication use was the predominant theme 30.78% (302), followed by pharmacy practice and pharmacist services 22.94% (225), and then pharmacy education and professional development 16.31% (160). The KSA, Jordan, Qatar, and the UAE were the leading countries to publish pharmacy practice research. Conclusions Pharmacy practice research is growing and significantly adding to enhance pharmaceutical health services in the Middle East Region. There is a need to develop a research agenda. This will help in enriching the practice, as well as to avoid repetitive ideas.